Studi Objek Wisata Alam Air Terjun Telun Berasap Kecamatan Gunung Tujuh Kabupaten Kerinci - Hidayani, Asma Tri (Pendidikan Geografi, 2014)
This study aimed to obtain the data, process, analyze and discuss the Study of Natural Attractions Niagara Telun Fuming Mount Kerinci District Seven in view of: 1) Management System, 2) How to Go / Enjoy Attractions, 3) Community Participation, 4 ) Sapta charm Conditions.This study belongs to qualitative research. informants in the study took the snowball technique, the research subjects or respondents that the Department of Tourism, Arts and Culture, Village Head Telun Fuming, business attraction, Village Community Telun smoky. Data collected through observation, structured interviews, documentation and shooting.The results showed: 1) attraction Telun smoky Falls is managed by the Department of Tourism, the management system is good enough, but there are still many that have not been repaired by the governments Department of Tourism, 2) how the visitor can enter / enjoy Niagara attractions that visitors wajub Telun Fuming pay admission to tourist sites, visitors on a regular day wear cost for children and adults Rp 2,000 to Rp 4,000, while a typical day like today Eid visitors are charged Rp 10,000, 3) Participation in the Village Telun Fuming society in maintaining attraction Telun smoky Falls by way of mutual cooperation in the tourist sites every Friday, and maintaining the security of the visitors come to the site every attraction. 4) The condition of hospitality, the beauty, the security, and the coolness Telun smoky Falls is very good, while the condition of order and memories Telun smoky Falls pretty good, but the hygiene conditions in Niagara Fuming unfavorable, due to the lack of awareness of visitors in maintaining the cleanliness The site attractions Telun smoky Falls.